Posseiros e possuidores : conflitos sociais na formação da estrutura fundiária em São Carlos-SP entre 1850 e 1888 - Silva, João Paulo da (2015)
This research has as its objective the analysis of the social conflicts during the process of land structuring of the region that currently comprises the city of São Carlos-SP, in the second half of the 19th century. The period of analysis, from 1850 to 1888, was chosen for being an important transition period in the country, marked, above all, by the Lei de Terras of 1850 and the abolition of slavery. It is also comprised within this time frame the early days of the transition of the production model in the region, away from the raising of animals and the production of foods destined for immediate necessities, to a model founded on coffee plantations, a model that already featuring capitalistic traits, modeled on a more disciplined and continuous work regime. The main documental scope that guides the research is a collection of civil lawsuits concerning land questions. Nonetheless, I combine the lawsuits with other sources, like land registries, censuses, Almanaques and journals. Despite sharing a semantic similarity, as well as a common etymological origin with the word “ownership”, “squatters” (“posseiros”) and “owners” (“possuidores”) will take on opposite meanings in the context of agrarian disputes of the 19th century: the former were stigmatized as poor invaders who did not have the means to make the land productive and to legalize it; the latter were the ones who, besides having ownership of the land, also possessed land titles. However, the construction of these categories is not as linear as it might seem at first sight. On many occasions, social and political prestige would supplant the necessity for proof of property titles. Small and medium-sized farmers had a hard time transforming their lands into legal property. Thus, I put forward the hypothesis that “posseiros” and “possuidores” are categories that, far from being fixed and having stable definitions, outline a historical process of conflict. In this way, I seek to comprehend the object of my research, in the light of the notions of primitive accumulation present in Marx, and most of all, in Thompson; and the notion of stigma, present in Goffman and Norbert Elias. I also intend to find out, with the chosen theoretical and empirical foundations, how a group of free laborers earned their place in the social dynamics of the region at the time.